Sodium content in major brands of US packaged foods, 2009. Issue 2 (26th November 2014) - Gillespie, Cathleen; Maalouf, Joyce; Yuan, Keming; Cogswell, Mary E; Gunn, Janelle P; Levings, Jessica; Moshfegh, Alanna; Ahuja, Jaspreet KC; Merritt, Robert
ABSTRACT: Background: Most Americans consume more sodium than is recommended, the vast majority of which comes from commercially packaged and restaurant foods. In 2010 the Institute of Medicine recommended that manufacturers reduce the amount of sodium in their products. Objective: The aim was to assess the sodium content in commercially packaged food products sold in US grocery stores in 2009. Design: With the use of sales and nutrition data from commercial sources, we created a database with nearly 8000 packaged food products sold in major US grocery stores in 2009. We estimated the sales-weighted mean and distribution of sodium content (mg/serving, mg/100 g, and mg/kcal) of foods within food groups that contribute the most dietary sodium to the US diet. We estimated the proportion of products within each category that exceed 1 ) the Food and Drug Administration's (FDA's) limits for sodium in foods that use a "healthy" label claim and 2 ) 1150 mg/serving or 50% of the maximum daily intake recommended in the 2010 Dietary Guidelines for Americans . Results: Products in the meat mixed dishes category had the highest mean and median sodium contents per serving (966 and 970 mg, respectively). Products in the salad dressing and vegetable oils category had the highest mean and median concentrations per 100 g (1072 and 1067 mg, respectively). Sodium density was highest in the soup category (18.4 mg/kcal). More than half of the products sold in 11 of the 20 food categories analyzed exceeded the FDA limits for products with a "healthy" label claim. In 4 categories, >10% of the products sold exceeded 1150 mg/serving. Conclusions: The sodium content in packaged foods sold in major US grocery stores varied widely, and a large proportion of top-selling products exceeded limits, indicating the potential for reduction. Ongoing monitoring is necessary to evaluate the progress in sodium reduction.